Konsep Manusia dalam Al-Qur’an Surat Al-Tin Pendekatan Tafsir Fazlur Rahman - Adi Ari Hamzah; Dedi Rismanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
Abstract The Nature of Man in the Al-Qur'an Al-Tin that, humans are superior humans (ahsani taqwim) humans are said to be superior when humans can exploit their potential for faith and goodness. Therefore, perfect physical and psychological conditions along with their potentials that need to be nurtured and developed in order to become noble beings and become ahsani taqwim (the best of creatures), because Allah will raise the degrees who believe and do good deeds, and vice versa Allah will lower the degree. people who do not believe and do good deeds. The epistemology used by Fazlur Rahman is Bayani, this epistemology is unique to Arabic thought which emphasizes the authority of the text as the main source and also uses other disciplines, nahwu, shorof, balghoh, fiqih, and kalam as tools in analyzing the text. And the nature of the Al-Qur'an is universal, the commentators in viewing the Koran are not usually intellectualists, but also use other approaches. So that the results of taking the law and the essence of the Koran do not experience ambiguity in taking a stand on the basis of the Qur'an, according to Rahman. The concept of man must be believed by Rahmatan Lil Alamin, Tafsir is a process not to be final and certain, but still requires. additions in accordance with the passage of time, so that the Qur'an will always be a source of concrete answers.